Upwind Discontinuous Galerkin Methods for Two Dimensional Neutron Transport Equations (Journal of Partial Differential Equations, 2020)
In this paper the upwind discontinuous Galerkin methods with triangle meshes for two dimensional neutron transport equations will be studied. The stability for both of the semi-discrete and full-discrete method will be proved.
Keywords: Upwind discontinuous Galerkin methods; Neutron transport equations; Stability